Isotopic Heterogeneity of Stem Water in Conifers Is Correlated to Xylem Hydraulic Traits and Supports Multiple Residence Times - Bowers, William H.; Williams, David G. (Frontiers in Water, 2022)
The isotopic composition of xylem water is frequently measured to identify sources of plant water uptake and evaluate the ecosystem water budget. The most common approach to sample xylem water is cryogenic vacuum distillation (CVD). However, the water recovered by CVD is total xylem water from the complex xylem tissue, including living xylem parenchyma cells, embolized tracheary conduits, and small or disconnected conduits that may have a different isotopic composition from water conducted through conduits of the dominant flow from roots to leaves. The isotopic composition of water in the dominant flow network is likely more representative of the isotopic composition of daily transpiration whereas the total xylem water likely integrates water with a longer residence time that may undergo exchange with organic compounds. An alternative extraction method using a pressure chamber (PC) can capture predominantly the transpiration-stream water through the dominant flow network. We compared the offsets in the isotopic composition of water recovered using CVD and PC from eight conifer species that vary in xylem anatomical and functional traits. The PC method accessed a significantly distinct isotopic domain of stem xylem water compared to the total xylem water accessed by CVD (2H, p = 0.012; 18O, p = 0.028). The difference between 2H of stem water extracted by PC and CVD methods (2Hstem) was significantly correlated with stem water content (p = 0.048) and the mean 2Hstem for each species had a significant relationship with species-specific xylem vulnerability to cavitation (i.e., ψ50) from literature values (p = 0.030). We found a significant positive relationship between 2Hstem and 18Ostem across all trees sampled (p = <0.001). These results support the existence of isotopically heterogeneous water pools, but we cannot exclude potential CVD artifacts contributing to a portion of the 2Hstem offsets. Our data suggest additional mechanisms of incomplete mixing and variable residence time in xylem conduits may contribute to isotopic heterogeneity proposed by previous work. Future work should consider using the PC method for assessing the isotopic composition of daily scale transpiration and determining species-specific xylem anatomical properties that could explain isotopic differences between various xylem water pools.